Impromptu : leading in the moment - Humphrey, Judith, 1943- (John Wiley & Sons, Inc., 2018)
Drawing upon the best impromptu moments from the Greeks to the present, this book shows you how to think on your feet and respond eloquently in every situation, and provides clear, actionable guidance to help you reach your full leadership potential. --